KINETIKA REAKSI HIDROLISIS ENZIMATIS SELULOSA MENJADI GLUKOSA DARI KULIT DURIAN (DURIO ZIBETHINUS RUMPH) MENGGUNAKAN ENZIM SELULASE - Maharani, Eka Ferdinda Putri Ayu; Agustina, Meri; Redjeki, Sri; Muljani, Srie; Pujiastuti, Caecilia (Jurnal Teknik Kimia, 2025)
The production of durian in Indonesia causes pollution of the environment by durian skin waste, so it is necessary to utilize durian skin. Durian skin contains 50-60% cellulose, 5% lignin, 5% starch, and other compounds.  The cellulose content in durian peel is utilized for making glucose by enzymatic hydrolysis method carried out under pH 5 conditions, 10% cellulase enzyme concentration, 50oC temperature, and 160 rpm stirring speed. Optimization of the enzymatic hydrolysis process depends on understanding the reaction kinetics that provide information about the reaction rate and conversion efficiency. This study aims to determine the reaction kinetics equation of enzymatic hydrolysis of cellulose to glucose from durian peel using cellulase enzyme and determine the effect of substrate concentration and hydrolysis time on product concentration. Substrate concentration and hydrolysis time have a directly proportional relationship to product concentration. At 5% substrate concentration and 180 minutes, the highest product concentration of 1.7% was obtained. This study was conducted with hydrolysis times of 60, 90, 120, 150, and 180 minutes and variations in substrate concentrations of 1%, 2%, 3%, 4%, and 5%. The conversion of enzymatic hydrolysis of cellulose to glucose at 1% substrate concentration was 69.43% with a reaction rate equation of